The Impact of Online Learning on the Students' Digital Communication Ethics - Jaisy, Ghozi; Wahyunengsih, Wahyunengsih; Rizki, Ahmad (Al-Azkiya: Jurnal Pendidikan MI/SD, 2022)
Communication in learning is very important because this supports children's success in learning. The better the communication that is built, it is hoped that the results will also be better. The purpose of this study was to analyze the impact of online learning on children's digital communication ethics. The object of this research is the students of SDN 07 Pagi from grades 1-3. The number of participants involved was 95 participants, the data used was by observing each class through Zoom Meeting media, from grades 1-3 for each child. In this study, we used a qualitative descriptive method with observation. The researcher acts as an observer and participates in teaching and learning activities for SDN 07 Pagi students through Zoom Meeting media. Students' responses to what the teacher said and how a student communicated in the class related to ethics became the focus. There are several classes observed. The purpose of observing from several different classes is because this online system has been carried out since 2019. The results of this study show the impact of students' digital communication ethics in class on teachers, parents, and students by looking at the differences between groups that have been online for 6 months, 1 year, and 2 years.